Optimalisasi Media Sosial melalui Digital Storytelling sebagai strategi Pemasaran Desa Wisata di Era Society 5.0 - Nida Urrahma Hidayati; Endang Widayati; Andreas Dian Anggi Kusuma; Tuti Panghastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Society 5.0 era, tourism villages are required to optimize social media as a strategic. This study aims to analyze and evaluate the effectiveness of social media, identify obstacles, and formulate a digital storytelling strategy. A combination method used with a concurrent triangulation strategy. The SOSTAC framework used to describe the marketing strategy. The research location was in Pancoh Ecotourism Village, with research objects consisting of Instagram and TikTok media content. The sampling technique used purposive sampling. Primary data were obtained through in-depth interviews with the head of the management and the marketing division, while secondary data consisted of documentation of social media content. Data validity was tested using triangulation. Qualitative analysis conducted by identifying digital marketing strategies and analyzing content. Quantitative analysis carried out by calculating the Engagement Rate on Instagram and TikTok to measure the effectiveness of audience interaction with narrative content. The results showed that Instagram was superior in strengthening promotional content through paid advertising, while TikTok demonstrated organic strength in human interest narratives and environmental education. Pancoh needs to develop a more balanced digital storytelling strategy, consistent content production, human resource training, utilizing social media algorithms, interaction patterns directed at two-way engagement, content distribution utilizing cross-posting techniques, scheduling uploads at prime time for young users, and placing the community as the main actor in the narrative